Torsade de Pointes/QT Prolongation Associated with Antifungal Triazoles: A Pharmacovigilance Study Based on the U.S. FDA Adverse Event Reporting System（FAERS）: A study of antifungal triazoles related to torsade de pointes/QT prolongation - Yu, Zicheng; Liao, Xiaolan (Journal of Pharmacy & Pharmaceutical Sciences, 2022)
Purpose: Torsade de pointes (TdP)/QT prolongation is a fatal adverse event (AE) when using antifungal triazoles. We aimed to compare the AE signals of TdP/QT prolongation and onset time among different drugs of this kind comprehensively. Methods: This retrospective research was to analyze the U.S. FDA Adverse Event Reporting System (FAERS) database containing 71 quarters of reports through online retrieval. We calculated the strength of signals of TdP/QT prolongation related to 4 drugs of triazoles by using the following indicators: reporting odds ratio (ROR), proportional reporting ratio (PRR), information component (IC), and empirical Bayesian geometric mean (EBGM). The onset time to the AE of TdP/QT prolongation among different antifungal triazoles were compared by using nonparametric tests. Management and visualization of the data were performed by employing MySQL Workbench and R software. The data information including clinical features, AE onset time, and outcomes were extracted for analysis as well. Results: After filtering the FAERS database, 448 reports were identified that were associated with TdP/QT prolongation when 4 triazoles played the primary suspected role. The AE signals of TdP/QT prolongation for any involved antifungal triazoles were detected by using the 4 detection indicators, and the signals of fluconazole are the strongest. This AE mostly occurred within 0-14 days after triazoles therapy. Conclusions: The AE signals of TdP/QT prolongation associated with antifungal triazoles were very intense. Attention must be paid to the TdP/QT prolongation of various triazoles, particularly at the early stages of antifungal triazoles treatment.